The effects of unilateral premature loss of maxillary primary molars on the dental arch dimensions - Dunia A Al-Dulayme (College of Dentistry/ University of Baghdad, 2013)
Background: The aim of the study was to evaluate the amount of changes in the horizontal and vertical maxillary arch dimensions measurements following the premature loss of primary molars. Materials and methods: The sample consist of (50) children with unilateral prematurely extracted either first or second primary molars at the mixed dentition stage. Results and Conclusions: Results shows that there was an increase in the vertical incisor to canine distance (A) with both premature loss of first & second primary molars due to distal movement of primary canines and at the same time there were a significant loss of space in the extraction space with premature loss of second primary molar due to a mesial movement of maxillary first permanent molars which at the same time tip lingually and this is clear obvious from the decrease in the inter-molars distances horizontally.